Beta-blockers in Cardiovascular Therapy: A Review - Camelia C. Diaconu; Dragos R. Marcu; Ovidiu G. Bratu; Ana Maria A. Stanescu; Gina Gheorghe; Andreea A. Hlescu; Dan LD. Mischianu; Maria Manea (Journal of Mind and Medical Sciences)
The role of beta-adrenergic receptor antagonists in cardiovascular therapy has been the subject of various studies over time, these agents representing one of the oldest class of drugs used for the treatment of cardiovascular diseases. Although beta-blockers have been excluded from guidelines as the first-line therapy in essential hypertension, they remain the first choice in patients with heart failure, coronary artery disease, and atrial fibrillation. In this article, we review the major clinical evidence for the use of beta-blockers in cardiovascular diseases. Several trials have demonstrated that beta-blockers reduce mortality in patients with heart failure with a reduced ejection fraction. Also, beta-blockers have beneficial properties in patients with heart failure with preserved ejection fraction. Guidelines recommend beta-blockers for the relief of symptoms in cases of angina pectoris and for the control of the ventricular rate in cases of atrial fibrillation. Also, beta-blockers have numerous benefits in hypertensive patients with diabetes mellitus. In conclusion, betablockers are an important class of cardiovascular drugs, reducing the mortality and morbidity rates in patients with cardiovascular diseases.